Sound radiation and transmission loss characteristics of a honeycomb sandwich panel with composite facings: Effect of inherent material damping. (24th November 2016) - Arunkumar, M.P.; Jagadeesh, M.; Pitchaimani, Jeyaraj; Gangadharan, K.V.; Babu, M.C. Lenin
Abstract: This paper presents the results of numerical studies carried out on vibro-acoustic and sound transmission loss behaviour of aluminium honeycomb core sandwich panel with fibre reinforced plastic (FRP) facings. Layered structural shell element with equivalent orthotropic elastic properties of core and orthotropic properties of FRP facing layer is used to predict the free and forced vibration characteristics. Followed by this, acoustic response and transmission loss characteristics are obtained using Rayleigh integral. Vibration and acoustic characteristics of FRP sandwich panels are compared with aluminium sandwich panels. The result reveals that FRP panel has better vibro-acoustic and transmission loss characteristics due to high stiffness and inherent material damping associated with them. Resonant amplitudes of the response are fully controlled by modal damping factors calculated based on modal strain energy. It is also demonstrated that FRP panel can be used to replace the aluminium panel without losing acoustic comfort with nearly 40 percent weight reduction. Abstract : Highlights: Equivalent stiffness properties of honeycomb core sandwich panel are calculated. Modal damping factors are calculated based on modal strain energy method. Resonant amplitudes are controlled by modal damping factor. 40 percent weight is reduced by replacing Aluminium panel to FRP panel.